Pengaruh Perbandingan Terigu dan Tepung Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Kue Pukis - Kristina Simanullang, Dwi Putri Natalia; Indri Hapsari Arihantana, Ni Made; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p13, 2023)
Pukis cake is a food made from flour, margarine, eggs, sugar, coconut milk, and yeast which is baked in a semi-circular mold. In making pukis cake, the filling is added using chocolate, jam, and cheese, so it has a savory and sweet taste. In the making of pukis cake the raw materials used are flour. Therefore, other raw materials are needed to reduce imports of flour and increase the nutritional value of pukis cake. This study was aimed to determine the effect ratio of flour and red bean flour on the characteristics of pukis cake and determine the best comparison of flour and red bean flour to produce pukis cake with the best characteristics. This study used a Completely Randomized Design (CRD) with a comparison of flour and red bean flour treatment consisting of 6 levels: 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, and 50%:50%. The treatment was repeated 3 times to obtain 18 experimental units. The data was analyzed by using analysis of variance, and if the treatment had a significant effect, then followed by Duncan Multiple Range Test (DMRT). The results showed that the ratio of flour and red bean flour had a significant effect on the water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, color, aroma, texture, taste, and overall acceptance (hedonic), color and texture (scoring). Pukis cake with a ratio of 80% flour and 20% red bean flour had the best characteristics, with water content 44,51%, ash content 0,08%, protein content 11,29%, fat content 17,03%, carbohydrate content 27,06%, crude fiber content 2,62%, slightly red color was liked, aroma was liked, soft texture was liked, taste was liked, and overall acceptance was liked.